2014
DOI: 10.5144/0256-4947.2014.65
|View full text |Cite
|
Sign up to set email alerts
|

Nasal bone length in Saudi rhinoplasty: a clinical-radiological study

Abstract: BACKGROUND AND OBJECTIVESHump reduction in the presence of short nasal bones can result in significant esthetic and/or functional problems in patients seeking rhinoplasty in the Middle East. The aims of this study were to determine the mean length of nasal bones, amount of nasal dorsum it forms in relation to the whole nose, and incidence of short nasal bones in the Middle Eastern population.DESIGN AND SETTINGSA prospective study that has been carried out in a tertiary care hospital.PATIENTS AND METHODSA total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…This conclusion is supported by Alharethy, who revealed that a straight nasal dorsum is the most desirable nasal profile in the Middle Eastern region, and that a posterior nasal dorsum within 2 mm is the most approved male nasal dorsum. 25 The findings of a study conducted by Yu et al also corroborate ours by showing that a straight dorsum is the most acceptable nasal form among both males and females. 17 The neoclassical cannons suggest that the most esthetically pleasing AW is equal to the intercanthal distance, 26 but we found that this ideal does not hold true for the female nose in the Middle Eastern region.…”
Section: Discussionsupporting
confidence: 82%
“…This conclusion is supported by Alharethy, who revealed that a straight nasal dorsum is the most desirable nasal profile in the Middle Eastern region, and that a posterior nasal dorsum within 2 mm is the most approved male nasal dorsum. 25 The findings of a study conducted by Yu et al also corroborate ours by showing that a straight dorsum is the most acceptable nasal form among both males and females. 17 The neoclassical cannons suggest that the most esthetically pleasing AW is equal to the intercanthal distance, 26 but we found that this ideal does not hold true for the female nose in the Middle Eastern region.…”
Section: Discussionsupporting
confidence: 82%
“…5 Three-dimensional computed tomography-based cephalometric measurements have been used to determine the variation in bone and soft tissue angles among men and women. 6 Moreover Alharethy 7 emphasized the integral role of the degree of nasal height on facial balance and harmony. Herein, we measured the angular anthropometric values of rhinoplasty seekers and compared them with the anthropometric measurements from the general population, previously collected by Al-Qattan et al 2…”
mentioning
confidence: 99%
“… 1 To the best of our knowledge, there has been no radiological analysis of nasal bone angles measurements in Saudi Arabia. 2 People of Arab origin have characteristic nasal features 2 and the popularity of rhinoplasty procedures has increased, so it is important for clinicians to understand not only ethnic differences but also the bony structures of the nose. Analysis of preoperative CT scans has shown a wide variation in lateral nasal wall anatomy and angulation.…”
mentioning
confidence: 99%